The cool runnings effect: Flexible citizenship, the global south, and transcultural republics at the Winter Olympic Games - Fabian, T. (The International Journal of the History of Sport, 2020)
As a pinnacle event in the global sporting calendar, the Summer Olympics have long been a site of flexible citizenship, whereby athletes sell their talents to the highest bidder. This trend in athlete labour migration has created transcultural national teams and threatened the legitimacy of the nation-state within the international sporting system. However, this trend has received little to no attention within the Winter Olympic context, in which the `athlete-mercenaries` tend to flow from the Global North to represent nations in the Global South. This new transcultural representation has not yielded Olympic success, rather narratives of inclusion and participation. Although these Winter Olympic newcomers are considered `exotic oddities,` they raise similar questions about nationhood and citizenship that their summertime counterparts do, albeit in the increasingly geopolitical context of the Global South. Flexible citizenship is an extension of the athlete migration trends that have become synonymous with globalization and economic liberalization and will remain a factor in international sport exchanges as long as the foundational unit of the system is the nation-state.